2016
DOI: 10.1002/jcsm.12155
|View full text |Cite
|
Sign up to set email alerts
|

Low skeletal muscle radiation attenuation and visceral adiposity are associated with overall survival and surgical site infections in patients with pancreatic cancer

Abstract: BackgroundCancer cachexia and skeletal muscle wasting are related to poor survival. In this study, quantitative body composition measurements using computed tomography (CT) were investigated in relation to survival, post‐operative complications, and surgical site infections in surgical patients with cancer of the head of the pancreas.MethodsA prospective cohort of 199 patients with cancer of the head of the pancreas was analysed by CT imaging at the L3 level to determine (i) muscle radiation attenuation (avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
169
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(195 citation statements)
references
References 57 publications
(108 reference statements)
12
169
7
Order By: Relevance
“…Outcome results in this analysis indicate that the median difference in survival in BRPC and LAPC patients is separated by a mere six months, like other findings in the current literature (35,70,71). Our study specifically included patients with only borderline resectable and locally advanced disease, which correlates with IIA, IIB, and III AJCC stages.…”
Section: Discussionsupporting
confidence: 66%
“…Outcome results in this analysis indicate that the median difference in survival in BRPC and LAPC patients is separated by a mere six months, like other findings in the current literature (35,70,71). Our study specifically included patients with only borderline resectable and locally advanced disease, which correlates with IIA, IIB, and III AJCC stages.…”
Section: Discussionsupporting
confidence: 66%
“…These results suggest that pretreatment PMI is useful for predicting outcomes for unresectable patients with APC undergoing systemic chemotherapy. Since the majority of previous reports have focused on the effect of skeletal muscle mass on survival for patients undergoing surgery, the results of the current study may be worth reporting (16,(19)(20)(21)(22)(23) (34) for baseline PMI may be attributed to the presence of advanced malignancies. Advanced malignancies themselves can cause severe muscle mass loss (17,18).…”
Section: Discussionmentioning
confidence: 92%
“…The proportion of SAEs of grade ≥3 in the PMI-H group was higher, as compared with in the PMI-L group, although the difference in the two groups did not reach significance in the present study. The majority of previous studies demonstrated that DSMM can increase the risk of development of surgery-associated complications for patients with PC (16,(19)(20)(21)(22)(23). Thus, caution for the development of SAEs during chemotherapy should be exercised, particularly in patients with PC with lower skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies [11,13,[20][21][22][23] [32], and 1 in China [26]. Among the included studies, 13 studies were directed at liver [11,13,[19][20][21][22][23][24][25][26][27][28][29] malignancy, 2 bile duct [30,31], 6 pancreas [12,14,[32][33][34][35], 2 periampullary [36,37], 4 periampullary and pancreas [38][39][40][41], and 1 hepatopancreatobiliary [42]. The sample size ranged from 67 to 763.…”
Section: Study Characteristicsmentioning
confidence: 99%